Program Kemitraan Masyarakat Melalui Penyuluhan Penyusunan Laporan Keuangan dan Pemasaran Digital di UD Artha Guna Sasih Bali pada Masa Pandemi Covid-19 - I Nyoman Sutapa; Ida Ayu Agung Idawati; Putu Arya Suryanditha (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service program aims to improve the ability of partners in compiling financial reports in accordance with applicable standards, increase the ability of partners to use digital marketing, and increase understanding about maintaining health when work in building stores. The implementation method is by providing training, counseling and mentoring. Subject in this program is Artha Guna Sasih’s owners and employees. Instrument of this program is using the shared questionnaire before and after execution. The evaluation stage is carried out by seeing whether there is an increase in understanding of the non-collectible receivables, the financial management field will provide counseling on how to do good marketing by utilizing digital marketing and the medical field will provide counseling on how to maintain health in the midst of a pandemic and hazardous substances contained in building materials such as cement. The results of the service will provide counseling on how to make non-collectible receivables, the financial management field will provide counseling on how to do good marketing by utilizing digital marketing and the medical field will provide counseling on how to maintain health in the midst of a pandemic and hazardous substances contained in building materials such as cement.